Modelo matemático para determinar a uniformidade de distribuição da água no sistema de irrigação por aspersão - Gomide, Reinaldo Lúcio; Bernardo, Salassier; Vieira, Manoel; C Sediyama, Gilberto (Revista Ceres, 2025)
In this paper, a methodology to calculate the uniformity of water distribution in a sprinkler system is presented. As a measure of this uniformity, the following expressions were used: Christiansen’s uniformity coefficient, the «new coefficient» of uniformity, pattern efficiency, statistical uniformity coefficient and the coeffici- ent of variability.